Effects of insulin-loaded chitosan-alginate nanoparticle on RAGE expression and oxidative stress status in the kidney tissue of rats with type 1 diabetes - Shirin Heidarisasan; Nasrin Ziamajidi; Jamshid Karimi; Roghayeh Abbasalipourkabir (Iranian Journal of Basic Medical Sciences, 2018)
Objective(s): Chronic hyperglycemia leads to activation of the advanced glycation end products (AGE)-receptor (RAGE) for AGE axis and oxidative stress, which promote diabetic renal damage. This study examines the effect of insulin-loaded trimethyl chitosan nanoparticles on the kidney tissue of diabetic rats. Materials and Methods: Twenty-five male Wistar rats were randomly divided into 5 groups: normal control (C), diabetic group without treatment (DM), diabetic group treated with chitosan-based nanoparticle (DM+NP, 1 ml by gavage), diabetic group treated with 8 IU/kg insulin-loaded trimethyl chitosan nanoparticles (DM+N.in, 1 ml by gavage), and diabetic group treated with 8 IU/kg trade insulin (DM+SC.in, 0.2 ml by subcutaneous injection). The animals were treated from weeks 8 to 10. At the end of the study, serum urea, creatinine, and uric acid were measured. Also, the level of AGE and RAGE mRNA expression, and oxidative stress markers were studied in the kidney tissue.Results: Insulin-loaded nanoparticles similar to trade insulin could significantly reduce urea, creatinine, and uric acid parameters, while the elevated total antioxidant capacity (TAC), thiol groups, and catalase activity also reduced total oxidant status (TOS) and malondialdehyde (MDA) levels (P